Continued implications of taxing roll-your-own tobacco as pipe tobacco in the USA. Issue Volume 24:Issue e2(2015) (10th April 2014) - Tynan, Michael A; Morris, Daniel; Weston, Tara
Abstract : Background: In 2009, a US$21.95 per pound disparity was created in the Federal excise tax between roll-your-own cigarette tobacco (RYO) and pipe tobacco in the USA. After this disparity was created, pipe tobacco sales increased and RYO sales declined as some manufacturers repackaged roll-your-own tobacco as pipe tobacco and retailers began to offer cigarette rolling machines for consumers to use. A Federal law was passed in 2012 limiting the availability of these machines, however, it was unclear what impact this law had on the sales of roll-your-own tobacco labelled as pipe tobacco. Methods: The quantity of RYO sold as pipe tobacco each month was estimated using objective data on Federal excise taxes. Results: From April 2009 through June 2013, 107 million pounds of RYO were sold as pipe tobacco, reducing Federal excise tax collections by US$2.36 billion. The amount of RYO taxed as pipe tobacco climbed steadily and then levelled off following the July 2012 Federal law. Conclusions: The Federal law did not correct the market shift that occurred in pipe and RYO sales beginning in 2009. Even without access to commercial rolling machines, smokers are continuing to take advantage of the tax disparity. Without a solution, states will continue to lose revenue, and smokers who would otherwise quit will continue to have a low-cost alternative product available for purchase. Potential solutions include: (1) US Treasury Department distinguishing between RYO and pipe tobacco based on physical characteristics and (2) changing the Federal excise tax so that RYO and pipe tobacco are taxed at the same rate.